Hungarian Monitoring, 7 June 1988 . [Magyar rádiófigyelő], 1988. június 7 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - UN extraordinary session - GDR wishes to pay reparations to victims of Fascism - Gherasimov evaluates Soviet summit - Young Fascists in Czechoslovakia Domestic Affairs: - Hungarian-American foreign relations - Várkonyi urges banning chemical and nuclear weapons at UN extraordinary session - Éva Marton becomes life member of Vienna Opera - Actress Hilda Gobbi receives distinguished award on her 75th birthday - Gabčíkovo-Nagymaros: archaeological findings at site to be flooded Külpolitika: - ENSZ rendkívüli ülésszak - Az NDK kártérítést kíván fizetni a fasizmus áldozatainak - Geraszimov értékeli a szovjet csúcstalálkozót - Fasiszta fiatalok ügye Csehszlovákiában Belpolitika - Magyar-amerikai külügyi kapcsolatok - Várkonyi szorgalmazza a vegyi és atomfegyverek betiltását az ENSZ rendkívüli ülésszakán - Marton Éva a bécsi Opera örökös tagja lett - Gobbi Hilda 75. születésnapján magas kitüntetést kap - Bős - Nagymaros: régészeti leletek az elárasztani kívánt területen